Epidemiology of paediatric elbow fractures: a retrospective multi-centre study of 488 fractures. (1st October 2019) - Okubo, H.; Nakasone, M.; Kinjo, M.; Onaka, K.; Futenma, C.; Kanaya, F.
Abstract: Purpose: Elbow fractures are common in children and occur during daily activities. The aim of this study is to evaluate the epidemiology of paediatric elbow fractures over a two-year period in Okinawa, a southern subtropical island in Japan. Methods: This was a retrospective study of 488 elbow fractures in children younger than 15 years old treated at 11 hospitals in Okinawa. Data included age, gender, calendar month, type of fracture, operation rate, mechanism of injury, and aetiology. Results: The most frequent age was 6 years old, with 47.5% of all elbow fractures occurring in an age range from 6 to 10 years old. The fracture rate for boys was 1.6 times higher than that for girls. The incidence was the highest in May (56 fractures) and the lowest in August (25 fractures). Supracondylar fractures were the most common type (44%), followed by lateral condyle fractures (22%); 45% of all fractures were treated operatively. Medial epicondyle fractures had the highest rate of operative treatment (91%). In the 6 to 10-year-old group, 19% of all fractures occurred while skateboarding or caster-boarding, the most frequent aetiology. Conclusions: Supracondylar fractures are the most common fracture type in 4 to 7-year-old boys. In the 6 to 10-year-old group, skateboarding and caster-boarding are the most frequent and increasing cause of elbow fractures. Therefore, some preventive measures are needed. Level of evidence: Level IV, case series